Les fours « à pain » dans les Gaules et les Germanies (ve s. av. J.-C.-ve s. apr. J.-C.), un regard technique - Nicolas Monteix; Camille Noûs (Gallia)
This article provides the first comprehensive overview of the different manifestations of tools used to bake previously ground cereals, in the form of “bread”, in Gallic and Germanic provinces, from the 5th c. AD to the 5th c. AD. The corpus of study includes 717 ovens, to which a history of techniques approach is applied. Without attempting to propose a typo-chronology of the ovens, and after having analysed the three main baking processes used during Antiquity, the evolution of the different forms taken by these processes is explored. In this article, bread is only mentioned in a generic manner, as it is not a distinctive feature of the ovens. Three techniques for baking flatbreads and breads were used in Antiquity. They can be distinguished according to the relationship between the dough to be baked and the fuel used for baking, as well as by the division or absence thereof between the hearth and the sole. As it is not specific to bread and cannot be identified by archaeology, cooking beneath embers is not mentioned here. In order to better understand the two forms of oven baking, a glossary of the different parts of the ovens is provided. The most important point in this technical and semantic analysis is to distinguish between the hearth, upon which a fire is lit, and the sole, which receives the products to be baked. The first ovens described are dome ovens and their study makes it possible to lay the foundations of bread baking in general. This study is based on ongoing experimentation following the reconstruction of a Pompeian bread oven at Saint-Romain-en-Gal. One of the 26 baking trials carried out between April 2016 and May 2019 is described in detail in order to track the different phases occurring as dough transforms into bread. The principle is to bake by heat accumulation, wherein the fuel is removed from the oven once a temperature of about 550°C is reached, as indicated by the whitening of the oven walls: the soot no longer deposits but is immediately incinerated. This is the first indication of the temperature increase, which can therefore be reproduced with certainty from one firing to the next. Once the fuel is removed, a short cooling phase of the oven is respected, and then portions of dough are introduced for baking thanks to the heat accumulated in the walls and sole. While the shape of the dome makes the oven energy-intensive, other features help to improve its energy capacity, such as a basalt ring at the base of the dome and a sole built of baked clay on a thick layer of sand. Subsequently, the different variations observed in the construction techniques of dome ovens are presented. Firstly, two major groups are highlighted and defined according to whether the construction requires the addition of exogenous materials to erect the dome. A distinction is thus drawn between ovens excavated directly in the substratum and built ovens. The different parts of the ovens are described: the hearth –which also serves as sole–, the –rarely hemispherical– dome, the mouth, the different materials used for construction, the possible base supporting the dome and finally the ancillary fittings (altar, vent, chimney and ashpit). Vertical hearth ovens represent the second major group of ovens. In this case, the hearth and sole are strictly separate. These ovens, which are depicted from at least the 7th c. AD onward, and which are still in use in some parts of the world, possess a firing process that is a combination of heat-accumulating and continuous combustion firing. After preheating, the fuel is not removed from the oven and the relatively thin dough pieces are pressed against the oven wall where they then bake. These ovens are therefore made up of two main components: a generally circular hearth on the one hand, and the body on the other. The body, which is ovoid or a truncated cone-shape in cross-section, is systematically open at the top, in order to introduce the portions of dough and to collect the resulting flat-breads. These ovens can be fixed, constructed with raw earth, or mobile, prefabricated earthenware, in which case they can be hard to identify. The traces left by these ovens can be tricky to interpret, especially as other ceramic culinary ovens, not suitable for baking bread, are now recognised. In general, the interpretation of a heating structure as a bread oven necessitates an absence of nearly any other type of evidence of use, i.e. traces linked to the working of metals or glass or of hearth vitrification. In the same way, basing one’s interpretation of an oven as a bread oven based on the discovery of plant remains is a technical contradiction. Before outlining the evolution of bread ovens in Gaul, it should be underscored that the various ovens included in the corpus do not all benefit from the same quality of data. Furthermore, the dates proposed in the maps representing the evolution of the distribution of the different oven types from the 5th c. AD to the 5th c. BC are sometimes very broad and thus require statistical weightings. The first dome ovens for baking “bread” are only attested to from the 4th c. BC. From then on, this type of oven was progressively introduced throughout the territory considered by this study, though it remains impossible to determine an exact zone of emergence, or to trace the geographical progression or rhythm of its adoption. Beyond certain fluctuations, the number of known ovens increases from the 2nd c. BC onwards, reaching two peaks in the third quarter of the 1st c. BC and in the last quarter of the 4th c. AD. At the same time, from the 4th to the 2nd c. BC, the size of the ovens gradually increased, subsequently stabilising and remaining constant until the 5th c. AD. However, in the 1st and 2nd c. AD, furnaces larger than 2 m in diameter appeared, which would correspond to a diversification of production needs. The study of the contexts in which the ovens were discovered allows us to better understand part of the chronology, as well as to highlight the existence of an increase in their number, paradoxically linked to transitory situations of disorganisation in the countryside. Finally, the small number of urban ovens associated with commercial bakeries is another remarkable detail.